IJERA 2022
DOI: 10.56896/ijera.2022.1.1.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CFD Results of Smooth Air Duct with Experimental and Available Equations in Literature

Abstract: "Solar air heater (SAH) has vast applications in agriculture, crop drying and other field. In solar air heater, air temperature increases at the exit section. Research has worked extensively in SAH field, experimentally and numerically to observe the performance of SAH. In the present work, a 3D model of SAH is created in Design Modeler of ANSYS and simulation is run in ANSYS Fluent for the Reynolds number range between 2000-18000. Main objective of the study is to calculate the Nusselt number (dimensionless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The research findings of these articles have implications for both theoretical fluid dynamics and practical applications involving such interfaces. 39,40 The study contributes to the understanding of fluid instability behavior in the presence of multiple concurrent processes, namely, velocity shear, heat transfer, and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The research findings of these articles have implications for both theoretical fluid dynamics and practical applications involving such interfaces. 39,40 The study contributes to the understanding of fluid instability behavior in the presence of multiple concurrent processes, namely, velocity shear, heat transfer, and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…As in the second, third, and fourth cases, electricity saving is 1.45 kWh, 0.7 kWh, and 1.01 kWh. So, from the Table 10, it is concluded that when solar intensity is more than 150 W/m 2 , this system will work efficiently and will improve building efficiency [47,[57][58][59][60][61][62].…”
Section: For Sahp Materialsmentioning
confidence: 99%
“…Study by Xu et al investigated the solar collector rectangular fins optimization with paraffin as energy storage medium to best heat transfer performance. Thermal Energy Storage (TES) systems can further can be implemented to further control the operations [34]. There are different methods adopted by the researchers to increase the efficiency of the solar system [35].…”
Section: Solar Energymentioning
confidence: 99%